Investigations on white spot disease outbreak in Penaeus monodon (Fabricius, 1798) in association with Vibrio mimicus infection in the Sunderbans, West Bengal, India - Raja, R. Ananda; Panigrahi, A.; De, Debasis; Kumar, Sujeet (Indian Journal of Fisheries, 2017)
The present study investigated the outbreak of white spot disease (WSD) in association with Vibrio mimicus infection, which occurred twice consecutively in a black tiger shrimp (Penaeus monodon) farm located in the Sunderbans, West Bengal, India. The farm stocked with post-larvae (PL) @ 16 PL m-2, encountered disease outbreak on the 41st day of culture (DOC) followed by a second outbreak on the 54th DOC with 100% mortality each time. Shrimp samples were collected for molecular diagnosis as well as for microbiological investigations. White spot syndrome virus (WSSV) infection was confirmed by polymerase chain reaction (PCR). V. mimicus isolated from the outbreak, was characterised by morphological, physiological and biochemical characteristics. V. mimicus isolated was found to be pathogenic by challenge studies which caused 100% mortality in P. monodon juveniles. Microbial load was studied in the natural infection and also in challenge trials in relation to the day of advancing infection. LD50 value for V. mimicus, isolated from the outbreak, was 107.32 in P. monodon juveniles. Co-infection of V. mimicus with WSSV led to 100% mortality within seven days from the onset of clinical signs.